Light at the end of the bottle: flourishing in people recovering from alcohol problems. (2nd January 2022) - Makin, Paul; Allen, Rosie; Carson, Jerome; Bush, Stacey; Merrifield, Bethany
ABSTRACT: Background: The field of positive psychology is fast growing and ultimately aims to increase flourishing. As yet, these concepts have had very limited impact in the field of alcohol dependence. The aim of this study is to compare flourishing levels in people recovering from alcohol problems with two comparison groups. Methods: An online survey was conducted with people recovering from alcohol problems (n = 107), a community sample of gym attenders (n = 185) and people with mental health problems (n = 130). They completed the PERMA Scale, as well as answering questions about their drinking. Results: People recovering from alcohol problems scored significantly better than the mentally ill sample on every aspect of the PERMA Scale. In contrast, they scored significantly worse on every subscale in comparison with the community gym attenders' group. Responses to open-ended questions highlighted the costs of alcohol problems, especially in terms of losses experienced through drinking, along with an unhealthy tendency to focus on the past. Conclusions: The abstinence model may reinforce a sense of hopelessness and powerlessness in those battling alcohol problems and may inhibit flourishing. There is a need to develop positive psychology interventions that may help individuals recovering from alcohol problems to flourish.